Evaluasi pengaruh konsentrasi umpan pada produksi biogas dari limbah cair industri alkohol secara fed batch - Dewi Astuti Herawati; Argoto Mahayana (Jurnal Rekayasa Proses, 2016)
Biogas is an alternative energy source that can be renewed as one of the solutions for the scarcity of fossil energy. Liquid waste from industrial bioalcohol production (technically termed as “vinasse”) is potentially one of very promising raw material of biogas. Vinasse has low pH value (4-5), which is not preferable for metanogen. Therefore this study aimed to define the optimum condition for the production of biogas. The variable to be studied in this research was the influence of vinasse to water ratios on the production of biogas in a fed batch reactor. Three ratios of vinasse and water with the ratios of vinasse to water as 1:2 (R1); 1:2.5 (R2); and 1:3 (R3) were studied. As much as 500 mL of raw material was fed to bioreactor with 6 L of cow manure as starter inoculums. The reactor was fed once every three days, with the feed input as much as 500 mL. At the beginning of the process, total solid suspended (TSS), volatile suspended solid (VSS) and chemical oxygen demand (COD) were analyzed. The volume of biogas was measured every day while the TSS and VSS values were measured once a week. The results showed that the production of biogas at R1 reached 1640.95 ml on day 9 with pH 7, CH4 concentration of 9.89% and CO2 level of 36.93%. The biogas production at R2 on day 20 reached 119.67 mL with a methane content of 15.85%, 43.282% of CO2 level, and pH 5. In R3 the volume biogas generated on day 10 reached 158.24 mL with CH4 content of 35.36%; 35.27% of CO2 level and pH 7. Fed batch system was shown to reduce the effects of inhibitor.